STRENGTH TRAINING IN PATIENTS WITH FIBROMYALGIA: A FEASIBILITY STUDY TREINAMENTO DE FORÇA EM PACIENTES COM FIBROMIALGIA: UM ESTUDO DE VIABILIDADE ENTRENAMIENTO DE FUERZA EN PACIENTES CON FIBROMIALGIA: UN ESTUDIO DE FACTIBILIDAD - Steffens R.A.K.* (2023)
© 2023, Redprint Editora Ltda. All rights reserved.Introduction: Fibromyalgia syndrome (FM) is characterized by the presence of diffuse pain lasting for more than three months and is often associated with sleep disorders. Studies have investigated the effect of strength training (ST) on pain and sleep quality in FM patients, but there continue to be diverse perspectives on the effects of this intervention in this population. Objective: The aim of the study was to examine the effects of strength training (ST) on pain and sleep quality in FM patients. Methods: Forty-eight women with FM participated in the study between August and October, 2012. Six (55±6.5 years) performed ST, conducted at Santa Catarina State University, and eight (47±9 years) comprised the control group. The Socio-Demographic and Clinical Questionnaire, the visual analog scale (VAS) for pain, and the Pittsburgh Sleep Quality Index were used. Data were collected before the first session and after the eight-week intervention and were analyzed using descriptive statistics and inferential tests. Results: The eight-week ST intervention decreased pain (p< 0.05) and significantly diminished the daytime sleep dysfunctions (p< 0.05), demonstrating that the proposed program contributes to improving patient quality of life. Conclusion: ST is a feasible treatment for patients with fibromyalgia. Level of evidence II; Therapeutic study.